Analisis Kebutuhan Siswa Kelas 3 terhadap Bahan Ajar Interaktif IPAS Berbasis Tri Hita Karana di Sekolah Dasar Negeri 2 Batur - Ni Komang Juli Reka Wardani; I Nyoman Sudirman; I Nyoman Ardana; I Nyoman Sujati (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to analyze the needs of grade 3 students at Batur 2 Elementary School for interactive teaching materials in Natural and Social Sciences (IPAS) subjects based on Tri Hita Karana. Tri Hita Karana is a local Balinese wisdom concept that emphasizes the harmonious relationship between humans and God (Parahyangan), humans and fellow humans (Pawongan), and humans and nature (Pabelasan). This needs analysis is important to understand how teaching materials that are integrated with local values ​​can help improve students' understanding of the material while forming characters that are in accordance with Balinese culture. The method used in this research involved observation, interviews with teachers, and questionnaires to students. The results of the analysis show that grade 3 students need teaching materials that are interactive, visual, and easy to understand, and relevant to their daily lives. Apart from that, teachers also need teaching materials that support project-based and collaborative learning. With interactive teaching materials based on Tri Hita Karana, it is hoped that students will not only gain academic science knowledge, but also be able to internalize local cultural values.